A quality assessment of online patient information regarding tonsillitis using the EQIP tool. (August 2022) - Kwan, Lok Yin; Yip, Ho Cheung Anthony; Tan, Sen; Fan, Ka Siu
Abstract: Background: Tonsillitis is a common paediatric condition. The decision to seek medical attention and consent to treatment is usually made by parents or guardians. With increased accessibility of the internet, online medical information plays an increasingly significant role in the decision-making process. Little is known regarding the quality of online patient information on tonsillitis, as this has not been previously studied. Objective: The aim of our study was to identify the quality of information regarding tonsillitis on websites intended for the public. Methods: We conducted a systematic review of online information on tonsillitis using the following search terms: "Tonsillectomy", "Tonsillitis", "Adenotonsillectomy" and "Tonsil". The first three pages of returned websites were captured and each website was examined using the validated Ensuring Quality Information for Patients (EQIP) tool (score 0–36). Results: A total of 92 websites met the inclusion criteria for analysis. The overall median EQIP score was 19 with an interquartile range of 17–22 and a maximum of 32. More than half of all websites originated from the USA (61%) and hospitals were the most common source of information (29%). Most websites failed to describe the quantitative benefits or address the medical intervention costs and insurance issues. Half of the websites included both tonsillectomy and antibiotics as treatments for tonsillitis. Only 68% included complications of tonsillitis or tonsillectomy. Conclusions: The assessment of the quality of online patient information websites regarding tonsillitis by the EQIP tool indicates that most websites were of poor credibility, with minimal information regarding treatment choices and complications. To improve awareness of tonsillitis, there is a need for more informative and patient-centred websites that are compatible with the international quality standard for patient information.